Tinjauan Yuridis Terhadap Tindakan Euthanasia dalam Perspektif Interkonektif - Wibowo, Sigit (Universitas Proklamasi 45, 2021)
The purpose of this study is to examine and determine the application of the law to the act of euthanasia in the perspective of the interconnectedness of Islamic law and Indonesian positive law. The research method used in this study is a normative juridical approach. This approach is intended to be a type of dogmatic research (doctrinal) and a form of prescriptive research in relation to laws. Furthermore, the research specifications are descriptive analytical, namely by describing the problems raised and providing analysis of the problems so as to be able to provide answers to these problems.The thesis statement of this research is that euthanasia in principle in all legal perspectives in Indonesia is an act that is prohibited, in the Criminal Code, namely passive euthanasia and active euthanasia. So that euthanasia is an act that cannot be implemented or has not been legalized because it is contrary to the Criminal Code, although the application of this article is felt to be very difficult in terms of proving it.In Islamic law, euthanasia is prohibited because life and death are the absolute right of Allah SWT and humans to always be ordered to maintain their lives with their endeavors when healthy or sick. Euthanasia, or killing without suffering until now has not been accepted in the values and norms that developed in society because it is not in accordance with the ethics adopted by the Indonesian people.